Development of Malaysian Ethnobotanical Online Database - Roshaizi, Nur Athirah; Omar, Mohd Shahir Shamsir; Mustapha, Aida (Journal of Sustainable Natural Resources, 2022)
The existing Malaysian ethnobotanical database is not sufficiently comprehensive and may hindersharing of ethnobotanical knowledge. The lack of interest and documentation especially in digitalizing priorknowledge is a worrying trend since Malaysia possess high ethnicity and abundance of biodiversity. It is crucial topreserve and digitalize the comprehensive ethnobotanical database as it gives benefits worldwide. This study aimedto identify online database features and data type for an ethnobotanical database, to collect and populate existingdatabase via secondary data and to test the acceptance of the database by users by testing whether the databasefulfil the requirements of a good ethnobotanical database. Rapid Prototyping method has been used in this studyinvolving User Requirement Analysis and data acceptance test to construct and create the best ethnobotanicaldatabase. MYETHBO is the database created by using the Omeka Classic management system with Darwin Corestandard. There are 1,074 plants information are collected online and mostly referred GlobinMed and GBIF. In thisstudy, 30 plant species has been setup as exemplar pages. This study successfully developed a comprehensiveethnobotanical database (MYETHBO) by being able to identify the database features and data type needed via theRapid Prototyping method, collect and populate existing data via secondary data and test the acceptance of thedatabase by distributing the questionnaire to lecturers. MYETHBO will be beneficial to researchers, students andpublic people to gain knowledge of ethnobotany. It is available at https://cercom.uthm.edu.my/myethbo/.